PENGGUNAAN JENIS DAN DOSIS PUPUK ANORGANIK DENGAN PENGAYAAN FESES SAPI PERAH PADA TINGGI TANAMAN SERTA PERBANDINGAN DAUN DAN BATANG SEGAR RUMPUT GAJAH (Pennisetum purpureum Schumach) - Wastiti, Rany; Hendarto, Eko; Hidayat, Nur (ANGON: Journal of Animal Science and Technology, 2022)
Background. This study aims to determine the best formula between the type and dose of inorganic fertilizer into dairy cow feces on plant height and the ratio of fresh stem leaves of elephant grass (Pennisetum purpureum Schumach). Materials and Methods. Dairy cow feces, inorganic fertilizers (Urea 540 grams, NPK 1,560 grams, and ZA 1,161 grams) with doses of 100 kg/ha/def, 200 grams each. kg/ha/def, 300 kg/ha/def, based on N urea content. The method used is an experimental factorial pattern with a completely randomized design (CRD) 9 treatments with 3 replications. The variables used were plant height and the ratio of fresh stem leaves. Quantitative data were analyzed using the analysis of variance test (ANOVA), then continued using the Continuing Test of Honest Significant Difference (BNJ) and Regression. Results. The results of the analysis of variance showed that the use of the type and dose of fertilizer did not interact so that it had no significant effect (F Hit < F Table 0.05) on plant height and the ratio of leaves and stems. Meanwhile, the fertilizer dose had a significant effect (Fcount > Ftable 0.05) or (P<0.05) on plant height. The results of the further regression test of the relationship between the dose of artificial fertilizer on plant height showed that there was a significant difference in each dose increase given. Conclusion. The use of the type and dose of inorganic fertilizer into the feces of dairy cows did not interact, increasing the dose resulted in a significant increase in plant height. Administration of inorganic fertilizer dosage levels gave an increase in elephant grass production, namely plant height.